Closing the circle: the knowledge management spiral of project management. (21st February 2007) - Jugdev, Kam
Using Nonaka's conceptual framework, we present empirical findings from a study on project management knowledge-sharing practices. Following a review of key concepts on competitive advantage and project management, we present our theoretical framework and methodology. The paper places our knowledge-sharing spiral findings in the context of an earlier multivariate study. Our findings support the Socialisation-Externalisation-Combination-Internalisation knowledge transfer model, as the majority of the correlations were highest as one moved between the four quadrants; the lowest correlation was between Externalisation and Combination. Although the correlations between the four modes of knowledge sharing did not consistently show strong enough relationships to support the view that project management as a whole was a source of temporary or sustained competitive advantage, the findings support the importance of emphasising knowledge development and sharing among all four quadrants.